The Use of Information & Technology (IT)-Based Learning Media in Islamic Religious Education Learning at SD Negeri 02 Nata, Bima Regency - Nurul Watoni (Universitas Muhammadiyah Enrekang, 2024)
The study of this problem is about the use of IT-based learning media (information & technology) in SD Negeri 02 Nata, Bima Regency. This research aims to: 1) describe teachers' abilities in the use of technology-based learning media; 2) what media are used by teachers in the teaching and learning process; 3) problems and solutions made by teachers to overcome the problems of using IT-based learning media in PAI learning in schools. This research is a field research that uses a qualitative descriptive method, namely by describing the research object as it is. The data collection method uses observation, interviews, and documentation studies. In checking the validity of the data, the researcher used triangulation techniques, namely: triangulation of sources, techniques and time. The findings of the study show that: 1) teachers are able to adapt to the times in using IT-based learning media, but their application is still not optimal; 2) in learning tools, teachers have used technology-based media even though it has not varied, but in reality, in the learning process teachers only teach conventionally; 3) Problems faced by teachers include several factors such as the lack of knowledge and skills of teachers, the geographical condition of the area that is included in the medium-weak internet power zone, to the personal factors of teachers who still have the habit of teaching without using learning media. However, teachers at SD Negeri 02 Nata can carry out their obligations well even though they are not fully supported by technology-based learning media to the maximum.